What if china’s path of development becomes a model for african countries - (:unkn) unknown (My University, 2020)
While we were still wondering about China, several political statements in Africa (such as South Africa, Rwanda, Ivory Coast, Senegal, etc) suddenly echoed. Almost all of them have nurtured the idea of aligning Africa _ or at least their countries _ with the Chinese model. China certainly offers an important example of an alternative to the westernization of development practice, but the very simplistic analyses made by 'researchers _ champions of the Chinese model' who sing the praises of China to push the countries of the South to blindly import the Chinese model as one would import food... _ is a factual error of analysis. What China offers is not a 'model' as such, but rather the proof of a pragmatism of institutional governance according to its history, culture, traditions, ambitions, needs, political context, the quality of its superstructure, its inventive capacity in the face of difficulty... China is, at last, a metaphor for 'otherness'. Model? Maybe so! But should it be copied? It's the background of this paper.
Keywords: African Research